Utterance-final particles in Klang Valley Malay - Hoogervorst, Tom G. (Wacana, Journal of the Humanities of Indonesia, 2018)
This paper examines a group of small morphemes analysed as “utterance-final particles” in the Malay variety of the Klang Valley, West Malaysia. It provides a preliminary investigation into their usage and diachronic evolution, connecting fieldwork-based findings with extant research on other Malay varieties. There is no univocal definition of utterance-final particles – known by other scholars as “discourse particles” or “pragmatic particles” – nor broad agreement on the term’s conceptual validity. Most previous research on Malay varieties approaches these units as unbound morphemes with no grammatical and little obvious lexical meaning, relegating their functionality to the realm of pragmatics. This study calls attention to data from Klang Valley Malay to demonstrate that particles cannot easily be divided into “grammatical” and “pragmatic” categories. Most utterance-final particles discussed here are etymologically derived from verbs, adverbs, interjections and other word classes and can at best be classified as “part-time” pragmatic particles. They display varying levels of grammaticality and pragmaticality depending on their intonation and syntactic position.